The role of MicroRNAs within extracellular vesicles in the creation of the pre-metastatic niche, for the development of prostate cancer metastasis to bone - Speakman, Abigail (2018)
In the UK in 2016, prostate cancer was the most commonly diagnosed cancer in men and it is the fifth most common cause of death due to cancer worldwide. 90% of these deaths are due to the development of metastatic lesions (most commonly in bone). The mechanisms which underpin the spread to bone remain to be determined. Communication of the primary tumour with the bone microenvironment may prepare the bone for metastasis through pre-metastatic niche formation. This project investigates this hypothesis through the determination of the role of extracellular-vesicle (EV) microRNA (miRNA) in the modulation of osteoblasts, the predominant cell type involved in osteoblastic prostate cancer bone metastasis. MicroRNAs (miRNAs) are small, single stranded RNAs, and are hypothesised to play a role in primary tumour communication with distant sites through altered regulation of transcription and translation in recipient cells. EVs released from primary tumour cells are likely important vehicles for the transfer of miRNAs and other signalling molecules to osteoblasts cells in metastatic sites. EVs originating from prostate cancer cell lines PC3, LNCaP and C4-2 and non-malignant prostate epithelial cell line PNT1A were used to investigate the transfer and subsequent function of miRNAs within an in vitro osteoblast cell line model (hOB). The data demonstrated the selective packaging of miRNAs into EVs, indicated EV content does not reflect cellular expression. The transfer of labelled EV-miRNA demonstrates the efficiency of miRNA transfer is also dependent upon the cell line from which the EVs originated. Furthermore, the data indicates other mechanisms of RNA regulation influence the resulting levels of EV-miRNAs within the recipient osteoblasts, but that EV-miRNAs are functional within recipient cells based on proof-of-principle evidence generated using Renilla-luciferase reporter assays. Finally, using global transcriptome analysis a number of biological pathways associated with osteoblast survival, differentiation and proliferation were found to be significantly modulated by prostate cancer (PC3) EVs compared to non-malignant controls (PNT1A). This study confirmed the role of miRNAs transported by EVs as important mediators of alterations in osteoblast gene expression which could aid with pre-metastatic niche formation. Understanding the methods of communication between the primary tumour and distant sites is an important step towards the development of potential therapeutics. Blocking tumour communication with distant sites may reduce metastatic tumour formation and therefore have the potential to improve patient prognosis. Further investigation is needed to confirm whether the findings of this study similarly applicable in vivo.